ANALISIS RASIO KINERJA KEUANGAN TERHADAP FINANCIAL SUSTAINABILITY BANK PERKREDITAN RAKYAT (BPR) DI JAWA TENGAH (Periode 2010-2014) - Rianasari, Septi; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2016)
This Research aims to analyze the influence of Return on Assets Previous Year (ð‘…ð‘‚ð´ð‘¡âˆ’1), NonÂ Performing Loan (NPL),Â Cash Â Ratio,Â Loan to Deposit Ratio Â (LDR),Â BankÂ Size, Â Deposit Mobilization and Bank Age to financial sustainability as measured by the Financial Sustainability Ratio (FSR). Case Study on Rural Banks (BPR) in Central Java during the period 2010-2014.The population of the research is rural banks (BPR) in Central Java during the period 2010-2014. 45 samples were taken by using purposive sampling method. The data used were obtained from the annual report of Rural Banks during 2010-2014. The analysis technique used is multiple linear regression analysis, statistical F-test, ststistical t-test, and classical assumption test that includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test.The results shows that the Return on Assets Previous Year (ð‘…ð‘‚ð´ð‘¡âˆ’1) has Â positive andÂ significant Â effect Â to Â Financial Â Sustainability, Â Non Â Performing Â Loan Â (NPL) Â has Â negative Â andÂ significant effect to Financial Sustainability, Cash Ratio has negative and significant effect to Financial Sustainability, Loan to Deposit Ratio (LDR) has positive and not significant effect toFinancial Sustainability, the Bank Size has positive and significant effect to Financial Sustainability, the Deposit Mobilization and Bank Age has negative and not significant to Financial Sustainability. The results of regression estimation shows the predictive ability of the model is 42.8%, while the remaining 57.2% is influenced by other factors outside the model.